MENINGKATKAN MINAT BELAJAR SISWA KELAS X SMK PRATAMA MULYA DENGAN METODE TWO STAY TWO STRAY PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Putri, Sabrina Aisyah; Maemunah, Siti; Nurhasanah, Siti; Farida, Nur Aini; Makbul, M. (HIBRUL ULAMA, 2024)
The lack of use of learning models causes a decrease in student interest and motivation in learning PAI subjects for class X students at SMK Pratama Mulya. Therefore, innovation in the use of effective learning models is needed. In this research, researchers tried to use the Two Stay Two Stray method to increase interest in learning in class. The Two Stay Two Stray method is a learning model where students learn to solve problems together with group members and two students from that group pass on information to other group members. This type of research is classroom action research and consists of two cycles. Cycle I is about Mahmudah material with subtitles (understanding, division of morals, propositions, and the nature of ghadab) the results obtained by students have not yet achieved learning completeness, so it is necessary to carry out syllabus II actions regarding Madzmumah material with the subtitle (implementation, examples, and lessons learned in self-control behavior) the results obtained by students are already achieve learning completeness, because students have understood the two stay two stray method.